THE PHENOMENON OF NATIONAL SECURITY IN THE HISTORY OF POLITICAL AND LEGAL DISCOURSE AND MODERN LEGAL DOCTRINE - Пікуля, Тетяна (SWorldJournal, 2024)
The article is devoted to the phenomenon of national security as an independent category in the history of political and legal discourse and in modern legal doctrine. The set of social and epistemological conditions are determined by the prerequisites th